R&D on a Nonlinear Dynamics Analysis Code for the Drop Time of the Control Rod - Daogang Lu; Yuanpeng Wang; Qingyu Xie; Huimin Zhang; Muhammed Ali (Science and Technology of Nuclear Installations)
Whether the control rod can drop down in time is one of the important guarantees for the safe operation of the nuclear power plant. The drop-down process of the control rod is very complicated. For a long time, the researchers have done a lot of work on that, but it is hard to consider all the nonlinear factors. This paper considers the main factors together. Based on the theoretical analysis, we developed the nonlinear dynamics response analysis software for the nuclear power plant, which can be used to calculate the rod’s drop-down time. Compared with the results of the experiments, the software we developed proves to be applicable and reliable.